Diagnoza stanu procesu zarządzania kadrami w organizacjach funkcjonujących w Polsce (trendy ewolucji) - Antczak, Zbigniew (The diagnosing personnel function (human resources management) an a company's functioning in Poland, 2007)
The results in the paper come from the autor’s scientific research and diagnosing personel function (Human Resources Management) in selected several hundred companies’ functioning in socio-economic transformations and globalized Polish economy. Apart from my own research, I have also made use of research of different authors and research which is commissioned by economic subjects. I have also used information which can be found in conference materials and Internet, statistical data and extensive internal documentation of many enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 241-255